2015
DOI: 10.3168/jds.2014-8925
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Validation of a system for monitoring individual feeding behavior and individual feed intake in dairy cattle

Abstract: The objective of this study was to validate an electronic system for monitoring individual feeding behavior and feed intake (Intergado Ltd., Contagem, Minas Gerais, Brazil) in freestall-housed dairy cattle. No data have been published that validate either the behavioral measurement or the feed intake of this system. Feeding behavior data were recorded for 12 Holstein cows over 5d using an Intergado system and time-lapse video. The cows were fitted with an ear tag containing a unique passive transponder and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 4 publications
2
39
0
1
Order By: Relevance
“…The inconsistency highlighted in data for some monitored cows most likely was due to a notable inter-individual variability between cows, different sensitivity to the threshold values selected to identify natural head tilt position, and from a small displacement of the data logger aluminium support during the monitoring (which modified the position of 3D-accelerometer respect to the cow's neck axis). The results from this study are similar to those from validation studies using video or visual observations as a control, which have shown high levels of correspondence between video recording and automatic monitoring devices when considering the total duration of behavioural activities (Müller and Schrader, 2003;Büchel and Sundrum, 2014;Chizzotti et al, 2015).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The inconsistency highlighted in data for some monitored cows most likely was due to a notable inter-individual variability between cows, different sensitivity to the threshold values selected to identify natural head tilt position, and from a small displacement of the data logger aluminium support during the monitoring (which modified the position of 3D-accelerometer respect to the cow's neck axis). The results from this study are similar to those from validation studies using video or visual observations as a control, which have shown high levels of correspondence between video recording and automatic monitoring devices when considering the total duration of behavioural activities (Müller and Schrader, 2003;Büchel and Sundrum, 2014;Chizzotti et al, 2015).…”
Section: Resultssupporting
confidence: 76%
“…Methods of assessing behavioural activity have changed in recent years, favouring automatic recording techniques. Automated recording devices for measuring feeding behaviour and feed intake of cattle are being used more and more widely (Krawczel et al, 2012;Bikker et al, 2014;Chizzotti et al, 2015). The development of automated monitoring systems that can continually and accurately quantify feeding behaviour could provide an early warning tool for efficient monitoring and control of modern and automated dairy farms.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency and accuracy of selection for feed utilization efficiency in livestock depends on the availability of large numbers of animals with high-quality feed intake records. As a consequence, there is now an increasing demand for a large database with feed intake as a phenotype for dairy and beef cattle breeding programs (Chizzotti et al, 2015), research on feed intake Reliability of breeding values for feed intake and feed efficiency traits in dairy cattle: When dry matter intake recordings are sparse under different scenarios E. Negussie, 1 * T. Mehtiö, 1 P. Mäntysaari, 1 P. Løvendahl, 2 E. A. Mäntysaari, 1 and M. H. Lidauer 1 7249 as a proxy for enteric methane production (Negussie et al, 2017), and precision livestock farming (Chizzotti et al, 2015). These all have motivated the generation and regular monitoring of feed intake on individual animals and on a large scale.…”
Section: Introductionmentioning
confidence: 99%
“…On-farm recording of feed intake from individual cows was practiced in tiestall barns with manual weighing out and weighing back of rations comprising separate feed items such as silage, sugar beets, hay, and concentrates (e.g., Mason et al, 1957). The process was laborious and over the years has been replaced by automated feeding stations with electronic scales and computerized recording (e.g., Bach et al, 2004;Chizzotti et al, 2015). Such complete schemes are characteristics of most traditional on-station daily recording systems.…”
Section: Introductionmentioning
confidence: 99%
“…Technology can be used to automate some types of monitoring. For example, in agricultural systems, radio frequency monitoring systems can accurately record feeding frequency, duration, and intake (see Chizzotti et al, 2015). Data from automatic systems have also been used to make inferences about social interactions (see Guzhva et al, 2016).…”
Section: Technical Notementioning
confidence: 99%